Manajemen Bimbingan Konseling dalam Mengatasi Kenakalan Siswa di Sekolah Menengah Pertama Al-Falah Kota Jambi - Anggraini, Rani; Sumirah, Sumirah; Atika, Atika (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze the management of guidance and counseling in addressing juvenile delinquency among eighth-grade students at SMP Islam Al-Falah. The study is grounded in management theory, which includes planning, organizing, implementation, and supervision, as well as guidance and counseling theory as a support service for developing students’ potential and resolving their personal and social problems. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that guidance and counseling management had been implemented through preventive, repressive, and curative programs in dealing with various forms of student delinquency, such as tardiness, violations of school regulations, and other deviant behaviors. The causes of delinquency were influenced by internal and external factors, including lack of parental supervision and negative peer environments. The main obstacles included limited counseling service time, a large number of students, and low student awareness of discipline. To address these issues, the school strengthened counseling services, enhanced collaboration with parents, and implemented character-building programs. Therefore, guidance and counseling management plays a strategic role in minimizing student delinquency despite facing several implementation challenges.